(untitled) (JURNAL GEOGRAFI, 2025)
This study investigates urban landscape changes in Surabaya from 2014 to 2024 using NDVI and NDBI indices derived from Landsat 8 OLI imagery. The Earth Engine platform was employed to generate cloud-free composite images, enabling detailed analysis of vegetation and built-up area changes. The methodology included a bivariate geovisualization technique to display areas of change, comparing NDVI and NDBI values over a decade to assess changes at a granular level. Results indicate that the ’Vegetation Stable - Built-up Area Stable’ category dominates, covering 2422 km², suggesting consistent land use in established areas. This dominance indicates well-established land use patterns across much of the city. Significant urbanization is observed in the ’Vegetation Decreased - Built-up Area Increased’ (70 km²) and ’Vegetation Stable - Built-up Area Increased’ (177 km²) categories, reflecting ongoing development pressures. These areas highlight zones of active development and environmental intervention. Additionally, a 75 km² increase in vegetation, particularly in coastal mangrove regions, highlights successful environmental management efforts. The study achieved an overall accuracy of 71%, demonstrating the effectiveness of NDVI and NDBI in capturing urban dynamics. While some classes require improved detection accuracy, particularly those involving decreased built-up areas, the model reliably identifies increases in vegetation and built-up areas.